2016
DOI: 10.1007/s12649-016-9613-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dissolved Organic Matter from Effluents in a Dry Anaerobic Digestion Process Using Spectroscopic Techniques and Multivariate Statistical Analysis

Abstract: Dissolved organic matter (DOM) collected from a garage-type dry fermentation system was investigated using UV-Vis absorption and fluorescence spectroscopy. Spectral parameters A 253/203 , biological index and fluorescence index were used to assess the structural characteristics and sources of effluent DOM. The results showed that aromatic rings highly substituted with hydroxyl, carbonyl, ester and carboxylic groups were obtained in the aerobic decomposition stage, and microbially derived organic matter dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 45 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Since this soil has been continuously exposed to excess sludge ponding, it is visually observed that physicochemical modifications have occurred in the soil structure and texture over the O‐horizon. [ 38 ] It is also believed that the degradation phase for the organic matter by the soil microbes under the ponded situation with excess sludge inflow can be rate‐limited as per the Monod's assumptions on food‐biomass ratio. However, the availability of nutrients in the soil after the organic amending depends on the biochemical and pedo‐climatic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Since this soil has been continuously exposed to excess sludge ponding, it is visually observed that physicochemical modifications have occurred in the soil structure and texture over the O‐horizon. [ 38 ] It is also believed that the degradation phase for the organic matter by the soil microbes under the ponded situation with excess sludge inflow can be rate‐limited as per the Monod's assumptions on food‐biomass ratio. However, the availability of nutrients in the soil after the organic amending depends on the biochemical and pedo‐climatic conditions.…”
Section: Resultsmentioning
confidence: 99%